HUMAN TRAFFICKING DAN SOLUSINYA DALAM PERSPEKTIF HUKUM ISLAM - Basri, Rusdaya (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2012)
This article discusses the problem of human trafficking and the solution in the perspective of Islamic law. Human Trafficking is